Multinucleon Transfer Channels in 86Kr + 124Sn Peripheral Collisions at 15 and 25 MeV/nucleon. - Fasoula, Olga; George A. Souliotis,; Stergios Koulouris,; Athena Pakou,; Martin Veselsky,; Sherry J. Yennello,; Aldo Bonasera, (HNPS Advances in Nuclear Physics, 2026)
Reaching the region of exotic neutron rich nuclei is on of the main interests in the nuclear community. Apart from fragmentation reactions and reactions below the Coulomb barrier another route to this region is through multinucleon transfer (MNT) and deep inelastic transfer reactions near the Fermi energy (15–35 MeV/nucleon). In this work, we present part of our detailed study of MNT reaction mechanisms on peripheral collisions between an 86Kr beam at 15 and 25 MeV/nucleon with a 124Sn target specifically on the momentum per nucleon distributions. The experimental data of these reactions were obtained with Momentum Achromat Recoil Separator (MARS) at Texas A&M University in previous works of our group. The interaction between the projectile and the target was simulated with the phenomenological Deep Inelastic Transfer model (DIT) and the microscopic Constrained Molecular Dynamics model (CoMD). The subsequent deexcitation of the initial excited projectile-like fragments was performed by the GEMINI model. Both models appear to describe the overall features of the data fairly well at 25 MeV/nucleon. This comparison of the model calculations with the experimental data at different energies aims to elucidate the evolution of the reaction mechanisms in this energy regime. We concluded that apart from independent nucleon exchange, target inelastic excitation and direct reaction processes involving neutron and proton pair transfer, cluster transfer and possibly meson-mediated charge exchange processes may be present. Along with recent work on reactions with a target of Ni in similar energy settings, we envision that the study of the momentum distributions will prove to be a useful tool in the elucidation of the reaction mechanisms that dominate the Fermi Energy regime.